A Systematic Review and a Meta-Analysis Comparing Prophylactic and Therapeutic Low Molecular Weight Heparins for Mortality Reduction in 32,688 COVID-19 Patients - Giossi, Riccardo; Menichelli, Danilo; Pani, Arianna; Tratta, Elena; Romandini, Alessandra; Roncato, Rossana; Nani, Alessandro; Schenardi, Paolo; Diani, Erika; Fittipaldo, Veronica Andrea; Farcomeni, Alessio; Scaglione, Francesco; et al. (Frontiers in Pharmacology, 2021)
Background. Antithrombotic treatment, including low molecular weight heparin (LMWH) or unfractionated heparin (UFH), has been proposed as a potential therapy for Coronavirus disease 2019 (COVID-19), to counteract diffuse intravascular clotting activation. However, it is unclear whether prophylactic or therapeutic doses are similarly effective in reducing mortality. Methods. We performed a systematic review (PROSPERO registration CRD42020179955) and meta-analysis including observational cohort studies and randomized controlled trials (RCT) evaluating the effectiveness of heparins (either LMWH, UFH, or fondaparinux) in COVID-19 patients. Heparin treatment was compared to no anticoagulation. A subgroup analysis on prophylactic or therapeutic doses compared to no anticoagulation was performed. Prophylactic dose was also compared to full dose anticoagulation. Primary endpoint was all-cause mortality. Secondary endpoints were major bleeding and length of hospital stay (LOS). Results. 33 studies (31 observational, 2 RCT) were included for a total overall population of 32,688 patients. Of these, 21,723 (66.5%) were on heparins. 31 studies reported data on all-cause mortality, showing that both prophylactic and full dose reduced mortality (pooled Hazard Ratio [HR] 0.63, 95% confidence interval [CI] 0.57-0.69 and HR 0.56, 95%CI 0.47-0.66, respectively). However, the full dose was associated with a higher risk of major bleeding (Odds Ratio [OR] 2.01, 95%CI 1.14-3.53) compared to prophylactic dose. Finally, LOS was evaluated in 3 studies; no difference was observed between patients with and without heparins (0.98, -3.87, 5.83 days). Conclusion. Heparin at both full and prophylactic dose is effective in reducing mortality in hospitalized COVID-19 patients, compared to no treatment. However, full dose was associated with an increased risk of bleeding.